ØªØ£Ø«ÙŠØ± Ø·Ù„Ø§Ù‚Ø© Ù‚Ø±Ø§Ø¡Ø© Ø§Ù„Ù‚Ø±Ø¢Ù† Ø§Ù„ÙƒØ±ÙŠÙ… Ø¹Ù„Ù‰ Ù‚Ø¯Ø±Ø© Ù‚Ø±Ø§Ø¡Ø© Ø§Ù„Ù†Øµ Ø§Ù„Ø¹Ø±Ø¨ÙŠ Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„ØµÙ Ø§Ù„Ø³Ø§Ø¨Ø¹ ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù…ØªÙˆØ³Ø·Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© "ØºØ²Ø§Ù„ÙŠØ©" Ø³ÙˆÙ…Ø¨ÙŠØ±Ù…ÙˆÙ„ÙŠÙˆ Ø¬ÙˆÙ…Ø¨Ø§Ù†Ø¬ - Isyatun Rodhiyah; Mu'at (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2021)
Arabic is an important language in human life. Arabic has a great influence in Indonesia, especially in Islamic boarding schools. Arabic is the language of the Qur'an which is the Qur'an as a way of life for Muslims. The purpose of this study was to determine the extent of the influence of fluency in reading the Qur'an on the ability to read Arabic texts for seventh grade students at MTs Ghozaliyah Sumbermulyo Jombang. This research uses quantitative research with correlational type. The results of the research in this study are the influence of fluency in reading the Qur'an on the ability to read Arabic texts for seventh grade students at MTs Ghozaliyah Sumbermulyo Jombang. This happens because of the "Tahfidz" program at MTs Ghozaliyah Sumbermulyo Jombang, where the program trains students in launching their reading in reading the Qur'an so that it greatly affects the ability of grade VII students in reading Arabic texts. Keywords: Fluency in Reading Al-Qur'an, Ability to Read Arabic Text